Study of pregnancy outcome in elderly gravida - Dixit, Pratibha V.; Mehendale, Madhuri A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Elderly gravida which is defined as age of mother as 35 years or more at the time of delivery has become increasingly common in last two to three decades. This accelerating demographic shift is of major clinical and public health concern, because advanced maternal age has consistently been associated with adverse pregnancy outcomes. Methods: An observational prospective study consisting of 120 pregnant women. All participants were divided into Study group and Control group. Results: Women of advanced maternal age have higher frequency of antenatal complications leading to early pregnancy termination and operative interference. There is significant increase in the incidence of adverse perinatal outcome due to preterm deliveries and NICU admission and neonatal death. Conclusions: With improved health services and better prospects of women who are >35 years of becoming pregnant, these pregnancies are fraught with complications. Women should realistically appraise the risks of pregnancy in later life. Hence these women should be counselled, and their complications managed with utmost care.